Bio‐synthesis of palladium nanocubes and their electrocatalytic properties. Issue 8 (2nd October 2018) - Peng, Xuwen; Cui, Zelin; Bai, Xuefeng; Lv, Hongfei
Abstract : The bio‐synthesis of palladium nanocubes (PdNCs) was realised using pine needle extract as the reducing agent and cetyl trimethyl ammonium bromide as the capping agent. As an eco‐friendly and readily available biomass, pine needle extract avoided the use of highly polluting chemical reducing agents. The growth process of PdNCs was analysed using ultraviolet–vis and Fourier transform infrared spectroscopy. Flavonoids, esters, terpenoids and polyhydric alcohols, which contain reductive groups, were mainly responsible for the transition of Pd 2+ ions to PdNCs. The morphology and structure of PdNCs were characterised using transmission electron microscopy (TEM), high‐resolution TEM, selected area electron diffraction and X‐ray diffraction. It was indicated that the as‐prepared PdNCs displayed a relatively high purity and good crystallinity with a face‐centred cubic structure and exhibited sizes ranging from 6.11 to 29.51 nm with an average particle size of 11.18 nm. In the methanol electro‐oxidation reaction, the PdNCs enclosed by 100 facets exhibited superior electro‐catalytic activity to commercial Pd/C, which was rarely reported in other bio‐synthesis processes for Pd catalysts. Meanwhile, the PdNCs showed excellent anti‐poisoning ability and long‐term stability. This study reveals the possibility of preparing shape‐controlled PdNCs with a specific structure and excellent electro‐catalytic activity.